Prevalence of self-reported suicidal thoughts in SLiCA. The Survey of Living Conditions in the Arctic ( SLiCA) - Broderstad, Ann Ragnhild; Eliassen, Bent-Martin; Melhus, Marita (Global Health Action, 2011)
The Survey of Living Condition in the Arctic (SLiCA) is an international research project on health and living conditions among Arctic indigenous peoples. The main objective of this article is to examine the prevalence of self-reported suicide thoughts among the study population in Alaska, Greenland, Sweden and Norway. This is a population-based survey. Indigenous participants aged 16 years (15 years in Greenland) and older living in traditional settlement regions in Alaska, Sweden and Norway and across the entire Greenland were invited to participate. Data were collected in three periods: in Alaska from January 2002 to February 2003, in Greenland from December 2003 to August 2006, in Sweden from spring 2004 to 2006 and in Norway in 2003 and from June 2006 to June 2008. The principal method in SLiCA was standardised face-to-face interviews using a questionnaire. A questionnaire had among other things, questions about health, education, traditional activities, ethnicity and suicidal thoughts. Information about suicidal thoughts, gender and age were available in 2,099 participants between the ages of 16 and 84 from Alaska, Greenland, Sweden and Norway. Greenland had the highest rates of suicidal thoughts when adjusting for age and gender (p=0.003). When stratifying on age and gender, significant differences across countries were only found for females in the two youngest age groups. Differences in suicidal thoughts across countries could partly be explained by educational level. Swedish respondents had less suicidal thoughts than those in any other countries. In the future, analyses of suicidal thoughts should take socioeconomic status into account as well as self- reported health, depression and anxiety.